2004
DOI: 10.1111/j.1399-543x.2004.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

The pancreatic ductal epithelium serves as a potential pool of progenitor cells

Abstract: With the increasing success of islet transplantation, beta-cell replacement therapy has had renewed interest. To make such a therapy available to more than a few of the thousands of patients with diabetes, new sources of insulin-producing cells must become readily available. The most promising sources are stem cells, whether embryonic or adult stem cells. Clearly identifiable adult pancreatic stem cells have yet to be characterized. Although considerable evidence suggests their possibility, recent lineage-trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(233 citation statements)
references
References 48 publications
12
217
0
4
Order By: Relevance
“…The population of ductal cells used in the present investigation has previously been described [21,24,28]. Thus, the expansion of cells derived from the islet-depleted exocrine fraction, which is usually discarded following isolation, has been shown to give rise to a near homogeneous population of CK19-positive epithelial cells, with minimal fibroblast contamination during the initial phase of culture [21,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The population of ductal cells used in the present investigation has previously been described [21,24,28]. Thus, the expansion of cells derived from the islet-depleted exocrine fraction, which is usually discarded following isolation, has been shown to give rise to a near homogeneous population of CK19-positive epithelial cells, with minimal fibroblast contamination during the initial phase of culture [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expansion of cells derived from the islet-depleted exocrine fraction, which is usually discarded following isolation, has been shown to give rise to a near homogeneous population of CK19-positive epithelial cells, with minimal fibroblast contamination during the initial phase of culture [21,25]. Although it is not possible to completely eliminate endocrine components from the initial plated material, previous studies have shown that such culture conditions are not conducive either to the adherence or prolonged survival of native islet cells [25] and that any endocrine cells that do exist become de-differentiated within 3-4 days of monolayer culture [24,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of Pdx1 in duct cells of the pancreas has also been observed following partial pancreatectomy in mice [85] and in insulin resistant Zucker fatty (ZF) rats [83]. Importantly in this regard, Pdx1 expression is often observed in proliferating duct cells [77,94,95], and such cells have been suggested to serve as substrate for β cell neogenesis, particularly in cases of adaptive hyperplasia or pancreas regeneration [92,[96][97][98][99]. A recent study suggests that Pdx1, in complex with TALE transcription factors, negatively regulates the duct-specific keratin 19 gene in mature duct cells [100].…”
Section: Role Of Pdx1 In Adaptive β Cell Hyperplasia and β Cell Regenmentioning
confidence: 99%